2020
DOI: 10.1101/2020.09.08.288092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning a genome-wide score of human-mouse conservation at the functional genomics level

Abstract: Identifying genomic regions with functional genomic properties that are conserved between human and mouse is an important challenge in the context of mouse model studies. To address this, we take a novel approach and learn a score of evidence of conservation at the functional genomics level by integrating large-scale information in a compendium of epigenomic, transcription factor binding, and transcriptomic data from human and mouse. The computational method we developed to do this, Learning Evidence of Conser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…We characterize the CpGs located on the mammalian methylation array regarding (a) CpG island status in different phylogenetic orders, (b) chromatin state analysis, and (c) LECIF score of evidence of human-mouse conservation at the functional genomics level 26 . (a) The boxplots report the median number (and interquartile range) of CpGs that map to CpG islands in mammalian species of a given phylogenetic order (x-axis).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We characterize the CpGs located on the mammalian methylation array regarding (a) CpG island status in different phylogenetic orders, (b) chromatin state analysis, and (c) LECIF score of evidence of human-mouse conservation at the functional genomics level 26 . (a) The boxplots report the median number (and interquartile range) of CpGs that map to CpG islands in mammalian species of a given phylogenetic order (x-axis).…”
Section: Resultsmentioning
confidence: 99%
“…exon, promoter, 5 prime untranslated region) and CpG island status (Supplementary Data). For human and mice we provide chromatin state annotations (Ernst and Kellis, 2012;Gorkin et al, 2020;Roadmap Epigenomics Consortium et al, 2015;Vu and Ernst, 2020) and the LECIF score on evidence of conservation at the functional genomics level between human and mouse (Kwon and Ernst, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minnoye et al ., 2020 discovered examples of orthologous enhancers that sequence-based methods failed to identify. Beyond sequence conservation, functional genomic annotations are important complementary information to determine orthology (Kwon and Ernst, 2021). Many studies have revealed the evolutionary landscape of genomes and epigenomes by comparing matched datasets across species (Villar et al , 2015; Gjoneska et al ., 2015; Vierstra et al, 2014; Cheng et al ., 2014; Brawand et al ., 2011; Odom et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%